Developing historical thinking skills and creativity of visually impaired middle school students - Akhan, Osman; Uzun, Adem (Frontiers in Psychology, 2025)
Since visually impaired students in Türkiye are subject to the general education curriculum, they may experience difficulties with the topics and activities included in the existing program. Especially in a subject like history, which involves abstract concepts, students can overcome these challenges more easily through activities specifically designed for them. In this context, the aim of the study is to develop the historical thinking skills and creativity of a group of visually impaired middle school students within the scope of the 5th grade “Journey to History” unit. The study is a qualitative research designed as an action research. The study group of the research consisted of 14 visually impaired 5th grade students, 5 girls and 9 boys, aged between 10 and 12, studying at a middle school for the visually impaired in Turkey in the 2022–2023 academic year. The data of the study were collected through face-to-face interviews with the students during the stages of the action research. The data obtained were transferred to the MAXQDA 2020 Plus qualitative data analysis program and analyzed with the descriptive analysis method and themes were created. According to the findings of the study, visually impaired students had the opportunity to develop their historical thinking skills and creativity. Students gained a deeper understanding of historical periods, chronological concepts and historical events. In particular, the processes that students learned by touching and feeling during museum activities improved their historical empathy and historical analysis skills. In addition to historical thinking skills, the activities also strengthened students’ creative thinking skills. Within this process, the students had been informed about the ancient civilizations of Anatolia and their historical contexts, and these pieces of information had been expressed by creative writings and animations. Students gained a significant improvement in historical thinking and creativity skills. Braille timelines and museum activities made it possible for students to comprehend abstract history concretely. It was an effective example to reduce the difficulties faced in front of visually impaired students while studying history. This study aims to emphasize the importance of accessible teaching practices that support the historical thinking and creativity skills of visually impaired students, while also contributing to both the curriculum and teacher training for inclusive history education.